2013
DOI: 10.5861/ijrsp.2013.367
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of Filipino values among forgiveness studies

Abstract: This paper reviewed 6 forgiveness studies that were made to understand Filipino forgiveness behaviors. The aim was to extract general Filipino values as well as the cultural values that Enriquez proposed in his theory of kapwa. Using combined qualitative and quantitative approaches in the research reports of those studies, the values that were salient in the experience of forgiving a transgressor were identified. Results showed that certain personal (open-mindedness and understanding) and interpersonal (smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Empathy in the frameworks of McCullough et al (1998) and Fehr et al (2010) was also found to be highly evident in Filipino forgiveness studies (Rungduin & Rungduin, 2013). Empathy is commonly defined as putting oneself in someone else's situation to understand the other person's feelings and experiences.…”
Section: International Journal Of Research Studies In Psychologymentioning
confidence: 95%
See 4 more Smart Citations
“…Empathy in the frameworks of McCullough et al (1998) and Fehr et al (2010) was also found to be highly evident in Filipino forgiveness studies (Rungduin & Rungduin, 2013). Empathy is commonly defined as putting oneself in someone else's situation to understand the other person's feelings and experiences.…”
Section: International Journal Of Research Studies In Psychologymentioning
confidence: 95%
“…Furthermore, similar to relational determinants of McCullough et al (1998), andFehr et al (2010), pakikisama or accommodative value was also found to be evident in forgiving others. Pakikisama strengthens the likelihood of granting forgiveness due to the feeling of being obligated to do it (Rungduin & Rungduin, 2013).…”
Section: International Journal Of Research Studies In Psychologymentioning
confidence: 98%
See 3 more Smart Citations